The application of TORS - into the larynx - Arkadiusz Standyło; Aleksandra Obuchowska; Justyna Wójcik; Alicja Ozga; Karolina Obuchowska; Piotr Trojanowski (Kazimierz Wielki University, 2020)
Laryngeal squamous cell carcinoma is one of the most common head and neck cancer, and it occurs more commonly in men than in women. The thought of losing phonatory and swallowing function has become the driving force of advancements in laryngeal cancer treatment. Transoral robotic surgery (TORS) is one of the fastest growing areas of head and neck surgery. This technology is assisted by remote-controlled miniaturized surgical instruments and magnified visualization with a high-definition three-dimensional camera. TORS is increasingly being used and was described in the context of laryngeal cancer surgery. It has been explored as minimally invasive surgery for supraglottic and glottic lesions, as well as for total laryngectomy. Transoral organ-preserving approaches have shown favorable oncologic and functional outcomes with good quality of life. Rapidly advancing TORS technique affords surgeons exceptional views of the larynx and hypopharynx with facile maneuverability in difficult to access areas. Thus, achieving negative margins and preserving normal laryngeal structures has become increasingly possible. The use of the robot for laryngeal cancer falls into three main categories:  supraglottic laryngectomy,  total laryngectomy and glottic cordectomy.            Transoral robotic surgery for laryngeal cancer has been shown to be feasible for minimally invasive partial laryngectomy for either supraglottic or glottic cancer, as well as for total laryngectomy, in selected patients. TORS supraglottic laryngectomy and TORS total laryngectomy have demonstrated good functional and oncologic outcomes.